Risk Perception, risk Involvement/Exposure and compliance to preventive measures to COVID-19 among nurses in a tertiary hospital in Asaba, Nigeria - Okwudili C. Ezike; Linda C. Odikpo; Evert N. Onyia; Michel C. Egbuniwe; Ifeoma Ndubuisi; Ada C. Nwaneri; Chikodili N. Ihudiebube-splendor; Chijike C. Irodi; Sambo B. Danlami; Amina W. Abdussalam (Elsevier, 2022)
Background: Covid-19 infection is a serious threat to health care workers (HCW) because it is primarily spread between people during close contact, often via small droplets produced by coughing, sneezing, or talking. Therefore, how HCW exposure to COVID 19 virus translates into risk of infection is thus critical for informing infection prevention and control (IPC) recommendations. Aim: This study assessed the risk perception, risk involvement/exposure and compliance to preventive measures to COVID-19 among nurses in a tertiary hospital in Asaba Nigeria. Methods: A cross-sectional descriptive survey (Census method) was used to recruit to the study, the entire 378 nurses in a tertiary hospital in Asaba, who met the inclusion criteria. There was no sampling as the population was few. For the participatory observation of the respondents, each ward had research assistant who is a nurse selected from the unit and trained on data collection for the study. Results: A subset of the nurses (9.3%) in the study centre strongly agree that Covid-19 is a mirage, and 2.6% also agree that the pandemic does not exist, while 37.8% agree that the pandemic is being politicized. Many of the nurses 141(37.3%) had contact with the environment where Covid-19 patients were cared for. For the participatory observation, decontamination of high touch surfaces was poor in most of the units. Personal protective equipment were lacking in some medical wards as only 2(50%) of the wards had all the PPE available at the time of the study. Conclusion: Some of the infection preventive measures for Covid 19 were neglected by the nurses, and this calls for reminder in the form of posters at strategic spots in the hospital and further trainings on IPC.